Evidence generation for the clinical impact of myCOPD in patients with mild, moderate and newly diagnosed COPD: a randomised controlled trial. Issue 4 (26th October 2020) - Crooks, Michael G.; Elkes, Jack; Storrar, William; Roy, Kay; North, Mal; Blythin, Alison; Watson, Alastair; Cornelius, Victoria; Wilkinson, Tom M.A.
Self-management interventions in COPD aim to improve patients' knowledge, skills and confidence to make correct decisions, thus improving health status and outcomes. myCOPD is a web-based self-management app known to improve inhaler use and exercise capacity in individuals with more severe COPD. We explored the impact of myCOPD in patients with mild–moderate or recently diagnosed COPD through a 12-week, open-label, parallel-group, randomised controlled trial of myCOPD compared with usual care. The co-primary outcomes were between-group differences in mean COPD assessment test (CAT) score at 90 days and critical inhaler errors. Key secondary outcomes were app usage and patient activation measurement (PAM) score. Sixty patients were randomised (29 myCOPD, 31 usual care). Groups were balanced for forced expiratory volume in 1 s (FEV1 % pred) but there was baseline imbalance between groups for exacerbation frequency and CAT score. There was no significant adjusted mean difference in CAT score at study completion, −1.27 (95% CI −4.47–1.92, p=0.44) lower in myCOPD. However, an increase in app use was associated with greater CAT score improvement. The odds of ≥1 critical inhaler error was lower in the myCOPD arm (adjusted OR 0.30 (95% CI 0.09–1.06, p=0.061)). The adjusted odds ratio for being in a higher PAM level at 90 days was 1.65 (95% CI 0.46–5.85) in favour of myCOPD. The small sample size and phenotypic difference between groups limited our ability to demonstrate statistically significant evidence of benefit beyond inhaler technique. However, our findings provide important insights into associations between increased app use and clinically meaningful benefit warranting further study in real world settings. A preliminary trial of a self-management intervention using a scalable, @NHS-approved app demonstrated signals of potential clinical benefit in a population of patients with mild–moderate and newly diagnosed #COPD over a 90-day period https://bit.ly/2PNDR8A